Genetic Algorithms for Parameter Estimation in Circadian Model - Janeiro, Fernando M. (2017)
This paper proposes an algorithm to estimate two parameter values vs, transcription of frq gene, and vd, maximum rate of FRQ protein degradation for an existing 3rd order Neurospora model in literature. Details of the algorithm with simulation results are shown in this paper.